Advances and Prospects of High‐Voltage Spinel Cathodes for Lithium‐Based Batteries. Issue 5 (15th February 2021) - Yu, Xingwen; Yu, Wiley A.; Manthiram, Arumugam
Abstract: Insertion compounds have been dominating the cathodes in commercial lithium‐ion batteries. In contrast to layered oxides and polyanion compounds, the development of spinel‐structured cathodes is a little behind. Owing to a series of advantageous properties, such as high operating voltage (≈4.7 V), high capacity (≈135 mAh g −1 ), low environmental impact, and low fabrication cost, the high‐voltage spinel LiNi0.5 Mn1.5 O4 represents a high‐power cathode for advancing high‐energy‐density Li + ‐ion batteries. However, the wide application and commercialization of this cathode are hampered by its poor cycling performance. Recent progress in both the fundamental understanding of the degradation mechanism and the exploration of strategies to enhance the cycling stability of high‐voltage spinel cathodes have drawn continuous attention toward this promising insertion cathode. In this review article, the structure–property correlations and the failure mode of high‐voltage spinel cathodes are first discussed. Then, the recent advances in mitigating the cycling stability issue of high‐voltage spinel cathodes are summarized, including the various approaches of structural design, doping, surface coating, and electrolyte modification. Finally, future perspectives and research directions are put forward, aiming at providing insightful information for the development of practical high‐voltage spinel cathodes. Abstract : Recent research progress in high‐voltage spinel cathodes (LiNi0.5 Mn1.5 O4, LNMO) has been reviewed. The structure–property correlations and the failure modes of LNMO materials are discussed. Recent advances in improving the cycling stability of LNMO cathodes are comprehensively summarized. Future perspectives and research directions toward the development of practical high‐voltage spinel cathodes are put forward.